Putting the Past into Perspective. Remembering, Reappraising, and Forgiving - Christopher Jude McCarroll (Revista de Estudios Sociales, 2023)
The process of forgiving seems to require that a person can remember a specific moment in their personal past in which they were harmed in some way. Forgiving, then, often requires episodic memory, which may be understood as memory of events or experiences in one’s personal past. What is it that grounds acts of forgiveness? One of the most prominent ideas is that, fundamentally, forgiveness involves a change in emotion; it requires that negative emotions associated with the event are abandoned, withdrawn or overcome. In this paper, we outline one way in which the emotion and meaning of past events may be modulated. In particular, we suggest that by thinking more abstractly about an event we can shift our emotional response to it. We outline one way in which this form of more abstract thinking, which can help us distance ourselves from the negative emotion associated with a past wrongdoing, can show up in memory. We propose that emotionally distant memories, or memories in which the emotional content has undergone some change, may often be recalled from an observer perspective, in which the individual recalls the event from an external or detached point of view. Recalling a past wrongdoing from an observer memory may help put it into perspective and afford the emotional distancing required to facilitate forgiveness.